The Influence of the Role of Parents as Educators and Peers on the Character of Discipline and Tolerance - Dayu Rika Perdana; Muhammad Nurwahidin; Loliyana Loliyana; Erni Erni; Amrina Izzatika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The aims of this study are to find out the influence of the role of parents as educators and peers on the character of discipline and tolerance. The type of research that researchers use is quantitative research. The result of this stusy shows that Based on the results of the research and discussion, it was concluded that there was a positive and significant influence on the role of parents as educators and peers on the character of discipline and tolerance of fifth grade students at SD Negeri Gugus R.A. Kartini East Metro District. Following are the complete results of data analysis. 1) There is a positive and significant influence on the role of parents as educators on the character of discipline and tolerance of fifth grade students at SD Negeri Gugus R.A. Kartini East Metro District, indicated by a correlation coefficient of 0.411 with a variable contribution of 16.89% is in the "Moderate" criteria. 2). There is a positive and significant influence on the role of peers on the character of discipline and tolerance of fifth grade students at SD Negeri Gugus R.A. Kartini, East Metro District, indicated by a correlation coefficient of 0.657 with a variable contribution of 43.16% is in the "Strong" criterion. 3). There is a positive and significant influence on the role of parents as educators and the role of peers on the character of discipline and tolerance of fifth grade students at SD Negeri Gugus R.A. Kartini, East Metro District, indicated by a correlation coefficient of 0.705 with a variable contribution of 49.70% is in the "Strong" criterion.